PENGARUH BUDAYA ORGANISASI DAN KARAKTERISTIK INDIVIDU TERHADAP KOMITMEN ORGANISASI PADA PT. NUSANTARA AUTO PARTS - Marvin Marvin; Latersia Br gurusinga (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study was to determine and analyze the work environment and career development effect on organizational commitment partially and simultaneously. The research used is research with quantitative methods. The technique of collecting data in this study was done by distributing questionnaires. The data analysis technique in this study used the classical assumption test, multiple regression, hypothesis testing with SPSS 22 software. The population in this study was 56 employees at PT. Nusantara Auto Parts. From the research results obtained tcount < ttable (6.606 > 1.68), meaning that the work environment has a significant effect on organizational commitment. Likewise with the career development variable obtained tcount < ttable (7.144 > 1.68), meaning that career development has a significant effect on organizational commitment. Based on the results of the F test, it shows that Fcount > Ftable (41.716 > 3.26) and a value of 0.000 < 0.05, this indicates that simultaneously the work environment and career development have a significant effect on organizational commitment.